'The Best Job in the World': Breadwinning and the Capture of Household Labor in Nineteenth and Early Twentieth-Century British Coalmining. Issue 1 (2nd January 2023) - Humphries, Jane; Thomas, Ryah
Abstract : This article explores the effects of gender inequality and women's disempowerment in the context of historical coalmining. Across the United States and Europe, ex-coalmining regions are characterized by significant deprivation. While there are many reasons for persistent problems, this study focuses on the restrictions imposed on women's involvement in economic life. Families in mining communities exemplified the male breadwinner structure, in which men's earnings supported wives and children who provided domestic services in return. Using evidence from Britain, this article exposes a different reality of household economics characterized by dominance and subordination: All family members were integrated into the coalmining production process and the creation of profit. Women's unpaid work did not simply provide domestic comfort; it transferred well-being from women and children to men and simultaneously contributed to the colliery companies' profits. These findings revise accounts of mining families while explaining the intransigence of deprivation in ex-coalmining areas. HIGHLIGHTS Women's disempowerment in historical mining communities had adverse effects that persist today. Pit women's labor propped up profits and wages and discouraged infrastructure investment. Breadwinning secured increased leisure time and higher income for men not women. Hours and incomes of "double shift"" factory women compare favorably to pit women. Regeneration must confront the gendered identities embedded in ex-mining communities.